Paying for open access - Lucas Stich; Martin Spann; Klaus M. Schmidt (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2021)
Open access (OA) publishing upends the traditional business model in scientific publishing by requiring authors instead of readers to pay for the publishing-related costs. In this paper, we aim to elicit the willingness to pay (WTP) of authors for open access publishing. We conduct two separate field studies with different methodological approaches in different scientific disciplines (economics and medicine). First, a choice-based conjoint (CBC) analysis measures stated preferences of 243 economists in Germany, Austria, and Switzerland regarding their valuations of open access publishing in the 'Top 5' economics journals. Second, a field experiment at four different open access medical journals elicits authors' self-determined ('Pay-What-You-Want') payments for open access publications. The results provide a plausible range of authors' valuations, given that the first study rather provides an upper bound and the second study a lower bound of authors' willingness to pay for open access publishing.
Keywords: D12; M31; L11; L82; 330; Open Access; Willingness to Pay; Choice-Based Conjoint Analysis; Pay-What-You-Want; Field Experiment